Leadership Analysis on the Financial Well-Being of MSME Entrepreneurs with Diffusion of Innovations as a Moderating Variable - Utami, Novia; Sitanggang, Marsiana Luciana (Politeknik Negeri Bengkalis, 2024)
This research aims to analyze the influence of leadership on the financial well-being of Micro, Small, and Medium Enterprises (MSMEs) entrepreneurs in Indonesia, with innovation diffusion as a moderating variable. Data were collected by surveying 400 MSME entrepreneurs who have been in business for at least six months. Data was analyzed using the Structural Equation Model (SEM) with the SEM-PLS program. The analysis results indicate that innovation adoption and leadership positively and significantly influence the financial well-being of MSME entrepreneurs. Additionally, innovation diffusion plays a significant moderating role in the relationship between leadership and financial well-being. The practical implication is that MSME entrepreneurs can enhance their financial well-being by adopting innovation and having effective leadership.